2005
DOI: 10.1029/2004jd005244
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of airborne carbonate over a site near Asian dust source regions during spring 2002 and its climatic and environmental significance

Abstract: [1] During spring 2002, three dust storm events were monitored by filter sampling in Xi'an near an Asian dust source region of northwest China. The carbonate (CO 3 2À ) fraction was determined by sample acidification and thermal evolution. The CO 3 2À accounted for 8.0 ± 0.8% of particles with aerodynamic diameter 2.5 mm (PM 2.5 ) during dust storms and 4.7 ± 3.0% of PM 2.5 between storms. The ratios of calcium to carbonate carbon were consistent with those of calcite (CaCO 3 ). The d C and d18 O abundances in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 59 publications
(66 reference statements)
9
100
2
Order By: Relevance
“…Spring samples were more scattered, indicating greater variability in acid-base balance. We noted that six springtime PM 1 samples that plotted below the equiline were rich in Ca 2+ , consistent with previous studies that have shown that high mineral dust loadings in spring can buffer aerosol acidity Cao et al 2005b). The remaining twenty-five spring samples plotted above the 1:1 line, showing they were acidic.…”
Section: Water-soluble Inorganic Ionssupporting
confidence: 75%
See 2 more Smart Citations
“…Spring samples were more scattered, indicating greater variability in acid-base balance. We noted that six springtime PM 1 samples that plotted below the equiline were rich in Ca 2+ , consistent with previous studies that have shown that high mineral dust loadings in spring can buffer aerosol acidity Cao et al 2005b). The remaining twenty-five spring samples plotted above the 1:1 line, showing they were acidic.…”
Section: Water-soluble Inorganic Ionssupporting
confidence: 75%
“…This ion has been used as an indicator of Asian dust, which typically exhibits its highest concentrations in spring (Choi et al 2001;Cao et al 2005b;Shen et al 2007). Prior studies revealed that fugitive dust in the downtown (i.e., dust from road traffic, construction activities, and traditional street sweeping) and soil dust from outside of downtown caused high dust loading in spring in Xi'an, and these lead to high Ca 2+ concentrations Shen et al 2008).…”
Section: Water-soluble Inorganic Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-range transport of Asian dust is one of the important sources of atmospheric aerosols in the downwind regions, particularly during the dust seasons. Asian dusts can influence ecosystems, environments, and climates (Sokolik and Toon, 1996;Sokolik et al, 2001;Han et al, 2004;Cao et al, 2005;Huang et al, 2006bHuang et al, , 2008. Some Asian dust may settle on the ocean's surface and provide nutrients (e.g., Fe 2+ ) to the oceanic biosphere (Zhuang et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of ion mass concentrations into micro equivalents was performed to calculate the cation/anion balance of PM 2.5 (Cao et al, 2005;Zhang et al, 2011;Tao et al, 2013). The cation and anion micro equivalents of particles were calculated as follows: The well balanced anion/cation (A/C) ratio must be 1.…”
Section: Ion Balance Calculationmentioning
confidence: 99%